Interleukin 3 : the panspecific hemopoietin - Schrader, John W. (Lymphokines, 1988)
Interleukin 3: The Panspecific Hemopoietin contains contributions from immunologists, hematologists, protein chemists, and molecular biologists whose efforts have defined the biology and molecular nature of interleukin 3 (IL-3) in less than a decade. The articles represent personal perspectives rather than exhaustive reviews. They are arranged in alphabetical order rather than thematically because many of the individual articles cover multiple aspects of the molecule. These articles cover topics such as the potential role of IL-3 in the pathology of allergic and inflammatory disease and the ro.